As características das praças da Regional Pampulha como suporte ambiental para idosos - Veridiana Rêgo Athayde Pinto (2022)
Leisure, as a human need, takes place in the articulations between cultural manifestations, social time/space and playfulness, it dialogues with the network formed by the different dimensions of life in society in which the individual is inserted. Conceived in Brazil as a social right, by the Federal Constitution of 1988, leisure can be understood as a tool that promotes health, understood as physical, mental and social well-being. In the current urban context, this condition can also be provided through the use of public leisure spaces intended for different social groups. An age group that has been growing exponentially worldwide is the elderly, which characterizes a picture of global aging. Considering that, in Brazil, there is also a growth in the number of elderly people, public leisure spaces are fundamental for the performance of activities of daily living performed by individuals of this age group, insofar as such spaces offer possibilities for the practice of these activities that collaborate to maintain the health, independence and autonomy of the elderly. Thus, understanding how these public leisure spaces, in this study represented by the squares, are characterized and their relationship as environmental support for the elderly is relevant so that actions to improve these squares can be formulated and implemented through public policies. Based on the above, the objective of this research is to evaluate the characteristics of the squares, through the questions of access and permanence, with the intention of suggesting possibilities to improve them so that they provide an adaptation to the needs of the elderly, making them more autonomous and independent. To achieve this objective, an observational quantitative methodology was adopted, based on a description scale that was applied in public squares, in the Pampulha Region, chosen based on the following criteria: (i) presence of an open-air gym and (ii) of 1000m². The data obtained were collected over a period of one month. These data were treated using Excel and its tools in order to reach an index that demonstrates how such spaces are appropriate to be used by the elderly, autonomously and independently. Only one square of the 21 (twenty-one) surveyed reached a value above 50% of the total value of the General index, which reflects the precarious conditions of access and permanence for the elderly in these spaces, characterizing a public problem. Keywords: Aging. Environmental Support. Leisure. Public policy. Squares.